Pemanfaatan Pelepah Pisang Menjadi Produk Inovatif sebagai Upaya Peningkatan Pendapatan Ekonomi Keluarga di Desa Jamberejo Kecamatan Kedungadem Kabupaten Bojonegoro - Nur Laila Rahmawati; Indah Fajrotuz Zahro; Asnawi; Nurul Fitriandari; Eryul Mufidah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
The economic challenge in the era of ASEAN Economic Community (MEA) is economic competition in the ASEAN countries. Consequently, efforts to improve Small and Medium Enterprises (SMEs) must be sustainable and should be done by synergizing among the social community, higher education, and the business community. To implement it, Jamberejo village of Kedungadem Sub-district, Bojonegoro developed assets that the social community has, that is banana bark which was able to be used as crafts that have economic value. By using Participatory Action Research (PAR) method, 57 women and higher education were invited to make crafts from banana bark to be used as a home industry business. Based on 6 samples of product, the business got a profit of Rp. 2,100,000. Return of Investment (ROI) is about 2.2 months. Then the average income level of the Jamberejo people has increased by 42.9% or equivalent to Rp. 900,000 per month. It happened after they got a mentoring program for the innovation of banana bark